2013
DOI: 10.1016/j.jalgebra.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Demazure crystals and tensor products of perfect Kirillov–Reshetikhin crystals with various levels

Abstract: In this paper, we study a tensor product of perfect Kirillov-Reshetikhin crystals (KR crystals for short) whose levels are not necessarily equal. We show that, by tensoring with a certain highest weight element, such a crystal becomes isomorphic as a full subgraph to a certain disjoint union of Demazure crystals contained in a tensor product of highest weight crystals. Moreover, we show that this isomorphism preserves their Z-gradings, where the Z-grading on the tensor product of KR crystals is given by the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The Fermionic form M (B, λ, w) is defined by the same formulas as (30)- (35). Theorem 4.2 11 is valid for D (1) n [34,31] and conjecturally valid for E…”
Section: Examplementioning
confidence: 99%
“…The Fermionic form M (B, λ, w) is defined by the same formulas as (30)- (35). Theorem 4.2 11 is valid for D (1) n [34,31] and conjecturally valid for E…”
Section: Examplementioning
confidence: 99%
“…The overlapping cases are the simply-laced affine root systems A (1) n , D (1) n and E (1) 6,7, 8 . It is known [8,9,11,17,18,36,37,43] that certain affine Demazure characters (including those for the simply-laced affine root systems) can be expressed in terms of KR crystals, which motivates the relation between P and X. For types A (1) n and C (1) n , the above mentioned relation between P and X was achieved in [21,25] by establishing a combinatorial formula for the Macdonald polynomials at t = 0 from the Ram-Yip formula [40], and by using explicit models for the one-column KR crystals [10].…”
mentioning
confidence: 99%
“…the perfectness conjecture). We say that the above tensor product B := N j=1 B r j ,s j is of level bounded by ℓ if ℓ is such that ⌈s j /c r j ⌉ ≤ ℓ for all j. Theorem 2.6 was generalized in [Nao13,Prop. 5.16] in the following way: when B (still of nonexceptional type) is a tensor product of level bounded by ℓ, and s j /c r j ∈ Z, then B ⊗ u ℓΛ 0 is isomorphic to a direct sum of Demazure crystals.…”
Section: Connected Components Go To Connected Components Under ψmentioning
confidence: 99%
“…When the (nonexceptional type) KR crystals in the tensor product are perfect of mixed levels, Naoi showed that one obtains a direct sum of Demazure crystals [Nao13]. In addition, this relationship was given for B r,1 in all types [Kas05] and can be extended to tensor products by the techniques of [Nao13] (see also [Nao12] for an alternative proof). Further connections of KR crystals, viewed as classical crystals, were described in [FL06,FL07].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation